Development and in vitro evaluation of a nanoemulsion for transcutaneous delivery. (March 2014) - Ledet, Grace; Pamujula, Sarala; Walker, Valencia; Simon, Shana; Graves, Richard; Mandal, Tarun K.
Abstract Objective: The purpose of this study is to develop a nanoemulsion formulation for its use as a transcutaneous vaccine delivery system. Materials and methods: With bovine albumin-fluorescein isothiocyanate conjugate (FITC-BSA) as a vaccine model, formulations were selected with the construction of pseudo-ternary phase diagrams and a short-term stability study. The size of the emulsion droplets was furthered optimized with high-pressure homogenization. The optimized formulation was evaluated for its skin permeation efficiency. In vitro skin permeation studies were conducted with shaved BALB/c mice skin samples with a Franz diffusion cell system. Different drug concentrations were compared, and the effect of the nanoemulsion excipients on the permeation of the FITC-BSA was also studied. Results: The optimum homogenization regime was determined to be five passes at 20 000 psi, with no evidence of protein degradation during processing. With these conditions, the particle diameter was 85.2 nm ± 15.5 nm with a polydispersity index of 0.186 ± 0.026 and viscosity of 14.6 cP ± 1.2 cP. The optimized formulation proved stable for 1 year at 4 °C. In vitro skin diffusion studies show that the optimized formulation improves the permeation of FITC-BSA through skin with an enhancement ratio of 4.2 compared to a neat control solution. Finally, a comparison of the skin permeation of the nanoemulsion versus only the surfactant excipients resulted in a steady state flux of 23.44 μg/cm2/h for the nanoemulsion as opposed to 6.10 μg/cm2/h for the emulsifiers. Conclusion: A novel nanoemulsion with optimized physical characteristics and superior skin permeation compared to control solution was manufactured. The formulation proposed in this study has the flexibility for the incorporation of a variety of active ingredients and warrants further development as a transcutaneous vaccine delivery vehicle.